Method of the Logistic Function for Finding Analytical Solutions of Nonlinear Differential Equations - N. A. Kudryashov (Моделирование и анализ информационных систем)
The method of the logistic function is presented for finding exact solutions of nonlinear differential equations. The application of the method is illustrated by using the nonlinear ordinary differential equation of the fourth order. Analytical solutions obtained by this method are presented. These solutions are expressed via exponential functions.logistic function, nonlinear wave, nonlinear ordinary differential equation, Painlev´e test, exact solution